2018
DOI: 10.1021/acs.jpclett.8b03247
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Wide-Bandgap Donor Polymer Enabling Annealing Free Nonfullerene Solar Cells with the Efficiency of 11.5%

Abstract: Substituting the hydrogen atoms on the conjugated side chain of a wide-bandgap polymer J52 with chlorine atoms can simultaneously increase the J sc , V oc , and FF of nonfullerene OSCs, leading to an efficiency boost from 3.78 to 11.53%, which is among the highest efficiencies for as-cast OSCs reported to date. To illustrate the impressive 3-fold PCE enhancement, the chlorination effect on the optical properties and energy levels of polymers, film morphology, and underlying charge dynamics is systematically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 48 publications
0
88
0
Order By: Relevance
“…[ 35 ] Chlorinated materials have also drawn attention due to their lower costs for the synthesis of target materials. [ 38–41 ] In comparison to fluorine and chlorine, very little attention has been paid to bromine in this area of research. Bromine is also a halogen atom and demonstrates a strong electronegativity and noncovalent interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] Chlorinated materials have also drawn attention due to their lower costs for the synthesis of target materials. [ 38–41 ] In comparison to fluorine and chlorine, very little attention has been paid to bromine in this area of research. Bromine is also a halogen atom and demonstrates a strong electronegativity and noncovalent interactions.…”
Section: Methodsmentioning
confidence: 99%
“…The BTIC‐2Br‐ m ‐based device exhibited a slightly higher V oc (0.88 V) compared with that of BTIC‐4Br (0.87 V) due to the higher LUMO energy levels. With a more efficient light harvesting, [ 38 ] the J sc of BTIC‐2Br‐ m may be significantly increased, up to 25.03 mA cm −2 . To the best of our knowledge, the PCE obtained in this study (16.11%) had the highest value among the brominated acceptors in binary PSCs.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, Hou et al designed and synthesized an efficient polymer PBDB-T-2Cl ( Fig. 3 ) from BDT-2Cl and BDD monomers [24] . They found that both fluorination and chlorination would produce nearly the same dihedral angles between the thiophene and BDT unit.…”
Section: Chlorination Of the Side Chain Of Benzodithiophene Unitsmentioning
confidence: 99%
“…Bulk heterojunction (BHJ) polymer solar cells (PSCs), comprising conjugated polymer as electron donor and fullerene or nonfullrene derivatives as electron acceptor, have been drawing extensive attentions because of their advantages of low cost, large-area solution processability, light weight, mechanical flexibility and the great potential for commercial applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Especially the nonfullerence polymer solar cells have shown a new direction for photovoltaic study due to the rapid development in PCE [21][22][23][24] . Various strategies on molecular design and synthesis for novel donor acceptor (D-A) polymers have been developed to facilitate the intramolecular charge transfer (ICT) [25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…
decades, heuristic approaches have been successfully used to enhance the performance of OSCs, including synthesis of new donor and acceptor molecules, [5][6][7][8][9][10] optimization of the interface and morphology, [11][12][13][14][15] ternary blending, [16][17][18][19] and device engineering. [20][21][22][23] As a result, power conversion efficiency (PCE) of OSCs has surpassed 15% for single-layer bulkheterojunction systems.
…”
mentioning
confidence: 99%